PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI BAPENDA MENGGUNAKA TOGAF - Selviana Yunita; Noorhikmah Fitriani; Febri Widianto (LPPM Unbaja, 2023)
The Regional Revenue Agency (BAPENDA) is an element that carries out supporting functions in the financial sector as well as co-administration tasks and the Regional Revenue Agency has the task of implementing regional policies in the field of regional tax revenue management where regional taxes are divided into two types: taxes managed by the state government and taxes managed by districts and cities. A tax manager, on the other hand, is run by a regional revenue agency or agency. The Regional Revenue Agency is an agency under and responsible to the Governor through the Regional Secretary of the Bappenda led by the Head of the Agency which is under and responsible to the Regent through the Regional Secretary. The Secretariat is led by a secretary who has the main task of assisting the Head of the Agency in carrying out the organization, administration, regional property, household, public relations, protocol, staffing, planning, performance and financial reporting. In planning the enterprise architecture at BAPENDA, Sampit City, the TOGAF ADM (Architecture Development Method) method is used as a system development guideline that will assist organizational activities. The enterprise architecture design includes the planning, design, implementation and maintenance of systems that will be used within the organization. This will ensure that the system used is in accordance with the needs of the organization and can assist in increasing efficiency and effectiveness in the organization's business activities.